Meshfree and finite element modelling of impact: A comparative study. (April 2016) - Kumar, V.; Ramamurthy, K.
Highlights: Comparison of FEM, SFEM and RKPM to predict impact has been studied for brittle and ductile materials. RKPM is better suited than SFEM and FEM to predict impact, penetration depth and residual velocity. SFEM and FEM are similarly suited for impact modelling. Abstract: Many methods have been developed in order to study the impact behaviour of solids and structures. Two common methods are meshfree method and the finite element method. The smoothed finite element method has become a powerful alternative to the finite element method as it promises to model large deformations and high mesh distortion without much loss of accuracy. In this manuscript, we present a comparative study of the finite element method, the smoothed finite element method and nodal stabilised reproducing kernel particle method with respect to their ability to predict impact events. The same constitutive models are applied for all computational methods. Through numerical examples, we show that meshfree methods can predict impact events most accurately but they are also computational more costly. We also show that the smoothed finite element method does not yield in an improvement compared to the finite element method. All results are compared to experimental data.